2008
DOI: 10.1002/cjoc.200890404
|View full text |Cite
|
Sign up to set email alerts
|

Flame Retardant and Smoke Suppressant of Fe‐Organophilic Montmorillonite in Polyvinyl Chloride Nanocomposites

Abstract: Two kinds of polyvinyl chloride (PVC)/organophilic montmorillonite (OMT) nanocomposites are prepared by a melt intercalation method. This study has been designed to determine if the presence of iron and zinc ions in the structure of montmorillonite (MMT) lattice can affect thermal, flame retardant and smoke suppressant properties. The information about the morphological structure of PVC/OMT nanocomposites was obtained using X-ray diffraction and transmission electron microscopy. The thermal and flame retardant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…It indicates that the smoke suppressant property of Fe-OMT is superior to that of Na-OMT in ABS/PVC blends, and the D s of ABS/PVC/Fe-OMT nanocomposites is depressed with the increment of content of Fe-OMT. Fe-OMT has a good synergistic effect on the flame retardancy and smoke density of PVC [35], which are in agreement with the TG results. Some similar results are also reported that the transition metals compounds are good synergistic agents in flame-retardancy of ABS and PVC [36,37].…”
Section: Flame Retardance and Smoke Suppressionsupporting
confidence: 91%
“…It indicates that the smoke suppressant property of Fe-OMT is superior to that of Na-OMT in ABS/PVC blends, and the D s of ABS/PVC/Fe-OMT nanocomposites is depressed with the increment of content of Fe-OMT. Fe-OMT has a good synergistic effect on the flame retardancy and smoke density of PVC [35], which are in agreement with the TG results. Some similar results are also reported that the transition metals compounds are good synergistic agents in flame-retardancy of ABS and PVC [36,37].…”
Section: Flame Retardance and Smoke Suppressionsupporting
confidence: 91%
“…However, the intercalation agent is combustible, resulting in negative effect on flame retardance. Besides, metal modified MMT was also used for its synergistic effect on improvement of flame retardance [29, 30].…”
Section: Introductionmentioning
confidence: 99%
“…[32][33][34] FeOMt containing both Fe 3+ and Zn 2+ could increase thermal stability and flame resistance of polyvinyl chloride (PVC) nanocomposites. 35 Both the peak heat release rate (PHRR) and the mass loss rate (MLR) were decreased when FeMt (1 to 5 wt%) was added to high impact PS, because Fe 3+ in FeMt might trap free radical and act as an antioxidant or free radical catching agent not only in the thermal degradation process but in the vulcanization process. 36 However, the comparative studies of different cation montmorillonites were even more rarely done.…”
Section: Introductionmentioning
confidence: 99%